Experiências de con-vivências de enfermeiros na linha de frente com a covid-19 - Sousa, Beatriz da Silva (2023)
The COVID-19 pandemic caused several impacts, mainly in the social, economic and health areas. In health, to face the pandemic, health professionals were involved to work in existing health services and in those in the field, built and/or improvised specifically to care for Covid-19 patients. In this way, health professionals, seen as the front line, were essential in assisting and caring for the population, however difficulties and adaptation needs arose in the face of the emerging situation. Thus, the objective of this study is to know the experiences of co-existence of nursing professionals on the front lines of COVID-19, through their perceptions and the use of photography. This is a qualitative research, which is part of a larger study, whose title is: Narratives and portraits of the front line: nursing and Covid 19. It was carried out in the municipalities of Ceará that form the Decentralized Health Area (ADS) of Sobral. The inclusion criteria were: professional nurses who worked on the front lines of the covid-19 pandemic, in the period from 2020 to 2021, comprising the municipalities of the ADS of Sobral, and the exclusion criteria were: professional nurses active in the pandemic, in actions strictly administrative, without direct contact with people suspected or diagnosed with Covid-19, or who did not understand the municipalities of the study. For this study, a questionnaire was applied and the participant was also instructed to portray through co-existence on the front line through a photograph. The speeches were analyzed using the Iramuteq qualitative data analysis software. This research respected the bioethical principles described in Resolution No. 466/12 of the National Health Council and was approved by the Research Ethics Committee (CEP) under opinion no. 4.211.833. In the context of the performance of activities by professional nurses in the face of the COVID-19 pandemic, most participants announced in their speeches how challenging it was. From another perspective, even in the face of the exhausting and challenging routine, the feeling of gratitude for playing the role of nurse also prevailed. The challenges in facing the COVID-19 pandemic were diverse, including the scarcity of information regarding the virus, the amount of material resources, work overload and the fear of contagion and of bringing the virus to their family members. Covid-19 frontline professionals experienced the greatest impact on their mental health, working during the pandemic proved to be a risk factor for symptoms of anxiety, depression, insomnia, anguish and fear. In the face of all the difficulties, there was still a weakness in offering emotional support to professionals. In this context, the greatest support came from the team and family, but spirituality was also present. It is concluded that, in addition to the scientific contribution, the results bring contributions in the historical context, as it allows us to observe photographs that refer to the COVID-19 pandemic period.